(untitled) (Educemara: Jurnal Pengabdian Masyarakat, 2025)
The results of interviews conducted with several teachers in Cluster III, Buleleng District, Buleleng Regency regarding writing scientific articles, were that there were still several teachers who had not been able to compose and publish scientific articles based on the results of the classroom action research they had carried out. One of the contributing factors is the lack of training in preparing scientific articles that they follow. Therefore, carrying out training in preparing scientific articles, especially from the results of the research they have conducted, is very important to carry out in Cluster III, Buleleng District, Buleleng Regency. The aim of this training activity is to improve the understanding and skills of teachers in Cluster III, Buleleng District, Buleleng Regency in writing scientific articles. The number of participants in this training was 24 people. This training activity will be carried out face to face. The data collection methods used to measure the success of this training are the training assignment method and questionnaires. Meanwhile, the data analysis method used is a quantitative descriptive data analysis method. An indicator of the success of this training is the increasing ability of teachers in Cluster III, Buleleng District, Buleleng Regency in compiling scientific articles, especially scientific articles from research they have conducted at school. Based on the training that has been carried out, it can be concluded that the ability of elementary school teachers in cluster III Buleleng District in compiling scientific articles has increased, after participating in the training activities that have been provided.